2010
DOI: 10.1021/ef101236h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on Water-in-Crude Oil Emulsion: Evaluation through Drop-Size Distribution Proxy

Abstract: A crude oil and a synthetic reservoir water are used to prepare water-in-oil emulsions. The droplet-size distribution of water-in-oil emulsions is measured by digitally processing optical micrographs. The time evolution of the droplet-size distribution is used as a proxy of emulsion stability. A procedure for obtaining homogeneous aliquots of the initial emulsion is developed. The procedure yields statistical replicas of the initial sample that allow one to measure size distributions through direct observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 31 publications
13
123
0
1
Order By: Relevance
“…These results are in agreement with those obtained by Fortuny et al (2007), who studied the effects of salinity, temperature, water content and pH on the stability of crude oil emulsions upon microwave treatment and found that the demulsification process was achieved with high efficiencies for emulsions containing high water contents, except when high pH and salt contents were simultaneously involved. Additionally, Moradi et al (2011) indicated that emulsions are more stable at lower ionic strength of the aqueous phase. …”
Section: Effect Of Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with those obtained by Fortuny et al (2007), who studied the effects of salinity, temperature, water content and pH on the stability of crude oil emulsions upon microwave treatment and found that the demulsification process was achieved with high efficiencies for emulsions containing high water contents, except when high pH and salt contents were simultaneously involved. Additionally, Moradi et al (2011) indicated that emulsions are more stable at lower ionic strength of the aqueous phase. …”
Section: Effect Of Salinitymentioning
confidence: 99%
“…Fortuny et al (2007) studied the effects of salinity, temperature, water content and pH on the stability of crude oil emulsions based on microwave treatment and showed that, in emulsions containing high water contents, the rate of demulsification is high, except when high pH and salt content were simultaneously involved. Additionally, Moradi et al (2011) studied the impact of salinity on crude oil/water emulsions by measuring the droplet-size distribution visualized by an optical microscopy method, and found that emulsions are more stable at lower ionic strength of the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Although no standard is available at present [22], the fact is that several methods rely on phase separation to quantify emulsion stability. In contrast, methods such as tracking evolution of drop-size distribution [24], can relate to pore-level mobility control mechanisms. In this article, we describe a number of stability proxies and provide a rationale for the choice of method for evaluating the impact of emulsions on EOR process efficiency.…”
Section: Evidence Of Emulsions Conformance Effects: Heavy-oil Eormentioning
confidence: 99%
“…While this might appear simple, for instance for microscopy methods, the challenge is to produce statistically equivalent samples for comparison purposes. This problem has been encountered before and a full description of one such a procedure can be found in reference [24]. In this sense, if for example centrifugal force is used to induce coalescence, all the drop-size distribution methods will have a similar pitfall as bottle tests.…”
Section: Electro-coalescencementioning
confidence: 99%
“…La tasa de penetración (ROP) en la industria del petróleo se define como la velocidad a la cual la sarta o broca del equipo perfora la roca subyacente para profundizar al pozo en busca del yacimiento estimado [1]. Perforar un pozo de petróleo depende del tiempo de renta de los equipos usados en la operación y cualquier propuesta metodológica que optimice tiempos de operación sin comprometer la seguridad del personal, la vida útil de la broca, la estabilidad del pozo o la trayectoria al objetivo tendrá un efecto positivo en la disminución de los costos de operación [2].…”
Section: Introductionunclassified